TOTEMISTIC MYTHS AND LEGENDS ABOUT THE WOLF IN UZBEK FOLKLORE - Isroilov, G`ayrat (FILOLOGIYA UFQLARI JURNALI, 2022)
The article describes the mythological views associated with the Wolf the views of the ancient Turkic peoples on the evolutionary variant of the totemistic imagination.